Efetividade da implantação de protocolos de prevenção de lesões por pressão: revisão integrativa da literatura - Vieira, Patricia Amanda (2019)
Among the worsening health conditions of hospitalized patients there is the development of pressure injuries. Nursing care for the patient with PI (pressure injuries) risk is still based on the individual knowledge of the nurse, routinely resulting in random and discontinued interventions. To improve the quality of nursing care, it should be supported by a scientific model and methodological reference. The pressure injuries prevention protocols are important instruments to conduct actions on the health care systems with the aim of improving the quality of care. The present investigation is an integrative review that aims to identify bibliographical productions about the effectiveness of the implementation of pressure injuries prevention protocols in hospitalized patients in hospital institutions. The selection of articles was made through the Virtual Library of Health and the sample of this review consists of eight articles regarding the elaboration, implementation and evaluation of pressure injuries prevention in hospital institutions. After analyzing the articles included in the review, the results of the studies indicated the existence of effectiveness in the implementation of prevention injuries protocols.